A Study of Students’ Perception: Identifying EFL Learners’ Problems in Speaking Skill - Ikrar Genidal Riadil (Universitas Teuku Umar, 2020)
Language is a pivotal aspect of human being. By learning, language people can communicate with each other, get information from one to another and interact. Unfortunately, in the real condition, it is still difficult for Indonesian students to practice their English ability in daily conversation. This paper will discuss the student’s perception within implementation problems and its solutions. The aim of this study is to identify the speaking problems experienced by EFL learners in speaking English. The researcher conducted this study using the qualitative research method. To gather the results, the researcher uses a questionnaire centered on the Penny Tang (1997) on speaking problems in learning a foreign language. The study’s data is collected from thirty-five students from Tidar University in Magelang. The result of the study is that the students have problems in learning speaking English. The most problematic for the students is mother tongue use, 77% students use their other tongue in English class and 83% agree that mother tongue is easier than English.